The propagation effect of paper version and the iPad version for periodicals - Cong Zhang; Yidan Sun; Zhongke Li (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Digital journal created a new development pattern. We use journal APP as an example to analyze how to migrate the journal content to Internet and other kind of media. Based on the case study of GQ and other fashion magazines, through text analysis, control experiments, in-depth interviews and other research methods, the authors analyzed the differences and connections between the iPad App and print edition of magazines, discussed the approaches towards operation of new media, offered the tendency of mobile device platform development for China's periodical publications. Design/methodology/approach: control experiment. Findings: The authors give a stance that the print edition of periodical publication will being alive still, and conclude that journal APP and printed version can be mutually beneficial and achieve a win-win state. And we believe that the journal APP is good at advertising propagation, which will accelerate the development of journal APP in such the information age, and such kind of media can integrate many information with variety of media forms. Research limitations/implications: Because of the limitation of technology, the authors only have the experiment on fashion magazine, which might to some degree simplify the issue under discussion. Practical implications: According to the conclusion of a series of experiments, we can imply the future of the media, and give the suggestion of both paper version and ipad version of the journal. Social implications: Since people can not live without media and media has to develope with the help of public, we have to give the new way of both sunrise media and sunset media. Originality/value: Based on the case study of GQ and other fashion magazines, through text analysis, control experiments, in-depth interviews and other research methods, the authors analyzed the differences and connections between the iPad App and print edition of magazines, discussed the approaches towards operation of new media, offered the tendency of mobile device platform development for China's periodical publications.
Keywords: 650; journal; iPad; App; GQ